Efektivitas Program Bantuan Dana CSR PT Semen Jawa Dalam meningkatkan Kesejahteraan Masyarakat Desa Kebonmanggu Kabupaten Sukabumi - Hermawan, Hernawati; Meigawati, Dine; Amirulloh, M. Rijal (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2024)
The purpose of this study was to find out how effective the CSR funding program for Kebonmanggu Village, Sukabumi Regency, was in improving the welfare of the local community. In order to approach this problem, a theoretical reference from Richard M. Steers is used. The data were collected through observation data, interviews, and documentation and were analyzed qualitatively. Based on the results of the study, it shows that 1. Optimization of objectives is quite effective in view of various CSR Corporate Social Responsibility activities in the form of environmental, economic and social. 2. The company's system perspective has not been maximized considering that the company does not really socialize with the community evenly, focusing more on communication with the government as a facilitator so that the community does not really understand CSR programs. 3. Human Behavior PT Semen Jawa has carried out an adaptive process considering that existing and future programs are in accordance with the main needs of the community. although it has drawbacks such as limited funds provided. The implementation of PT SCG's CSR program in Kebonmanggu Village is seen from the perspective of the Sukabumi Sukabumi Regency Regional Regulation Number 6 of 2014 concerning Corporate Social Responsibility, Partnerships and Community Development. It can be said that it has been effective, but in practice it has not run optimally.